NESCoM Research Report (2019) - Costalonga, Leandro; Coura, Daniel; das Neves, Marcus Vinícius; Costa, Fabiano; Rocha, Helder (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10437, 2019)
The NESCoM is a multidisciplinary research center formed by musicians, engineers and computer scientists. The main research interest lies with sonology, audiotacticle musical analysis, ubiquitous music, interactive multimedia installations, and the design of computer music technology in general. Overall, the common ground for the NESCoM projects lies with the human-aspects, both cognitive and motor, behind a musical activity. This can come, for instance, in the shape of an audiotactile analysis of musical interaction applied to a new digital musical interface designed to overcome human physical constraints or the composition of a cinema soundtrack based on perceptual models of the audience. In this paper, it is reported a short description of the ongoing projects of the NESCoM and the future works.